Outcome of Dual 90-90 Plating in Intercondylar Fractures of Distal Humerus in Adults - Shrestha, Dinesh; Shrestha, Merina (Journal of Nepalgunj Medical College, 2018)
Background: Intercondylar fracture of distal humerus are very difficult to manage. It needs proper anatomic reconstruction and rigid fixation. Aims and Objectives of study: Evaluation of outcome of dual bicolumnar 90-90 plating of AO type 13C fractures of distalhumerus in adult. Material and method: In a prospective hospital based study on 16 patients with a mean age of 33.37 years ± SD8.30, who presented with intercondylar fracture of distal hummers were studied between July 2015 to December 2017. All patients were graded according to AO classification. Out of 16 patients 5 were in 13C1, 6 were in 13C2 and 5 were in 13C3 subgroup. All patients underwent open reduction through Chevron olecranon osteotomy and fixation was done with dual plating in 90-90 fashioni.e.; 3.5 reconstruction plate posterior and 1/3 tubular plate from medial border. We used the Mayo elbow performance score system for evaluating our results. Results: The mean follow up period was 9.38 months. All fractures healed uneventfully. Two of five patients with 13C3 fractures and two of six patients with 13C2 fractures has flexion deformity of less than 30*. Average range of motion was 95*(range 60*-130*). The Mayo elbow performance score was excellent in 7, good in 7 and fair in 2 patients. Conclusion: Dual 90-90 plating technique through Chevron olecranon osteotomy is a good method for intercondylar reconstruction with rigid fixation like AO 13C fractures.